Comparative stability of perpendicular versus parallel double-locking plating systems in osteoporotic comminuted distal humerus fractures - Stoffel, Karl; Cunneen, Sam; Morgan, Robert; Nicholls, Rochelle; Stachowiak, Gwidon (John Wiley & Sons, Inc., 2008)
In distal humerus fractures, the restoration of stability is important to allow early mobilization and hence more favorable functional outcomes. In this article, we compare the biomechanical stability of perpendicular and parallel locking plating systems for the internal fixation of AO Type C2 distal humerus fractures in osteoporotic bone. Fractures were simulated in paired cadaveric bones and fixed using either the perpendicular 3.5 mm LCP distal humerus plating system (Synthes; Sydney, Australia) or the parallel Mayo Clinic Congruent elbow plate system (Acumed; Hillsboro, OK), using locking screws in both systems. Both systems were then tested for their stiffness (in compression and internal/external rotation), plastic deformation, and failure in torsion. Comparatively, the parallel locking plate system provided a significantly higher stability in compression (p = 0.005) and external rotation (p = 0.006), and a greater ability (p = 0.005) to resist axial plastic deformation. Stability for both constructs appeared to be dependent on bone quality, however the stability of the perpendicular system was generally more sensitive to bone mineral density, indicating a possible need for additional independent interfragmentary screws. A disadvantage of the parallel locking plate system was wear debris produced by its tapping system. In summary, the biomechanical findings of this study suggest that both locking plate systems allow early mobilization of the elbow in patients with osteoporotic bone following fixation of a comminuted distal humerus fracture. However, the parallel locking system showed improved stability compared with the perpendicular locking system, and therefore may be more indicated.